2018
DOI: 10.2147/cmar.s182105
|View full text |Cite
|
Sign up to set email alerts
|

STAT1 inhibits STAT3 activation in esophageal squamous cell carcinoma

Abstract: BackgroundSignal transducer and activator of transcription (STAT) 1 is an important transcription factor and has been reported to be a tumor suppressor in many types of cancer. However, another STAT family member, STAT3, is considered to be an oncogene. The cross-talk between STAT1 and STAT3 in cancer has not been fully demonstrated.Materials and methodsEsophageal squamous cell carcinoma (ESCC) was used as a model to examine STAT1-STAT3 cross-regulation in cancer. We detected STAT1-STAT3 binding by co-immunopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Conversely, a recent study has demonstrated that murine OSM phosphorylates STAT3 via gp130/LIF activation but not STAT1 causing specific regulation of STAT3 responsive genes in primary osteocytes (68). Indeed, STAT3 itself is capable of interacting with other STATs; STAT1 for example has been demonstrated to exhibit inhibitory effects against STAT3 signaling in a study on esophageal squamous cell carcinoma (69). Thus, a clearer understanding of the various cues directing this complex transcriptional landscape is vitally important.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a recent study has demonstrated that murine OSM phosphorylates STAT3 via gp130/LIF activation but not STAT1 causing specific regulation of STAT3 responsive genes in primary osteocytes (68). Indeed, STAT3 itself is capable of interacting with other STATs; STAT1 for example has been demonstrated to exhibit inhibitory effects against STAT3 signaling in a study on esophageal squamous cell carcinoma (69). Thus, a clearer understanding of the various cues directing this complex transcriptional landscape is vitally important.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that STAT3 interacts with other STATs in conjunction with ER, such as STAT5, which has some opposing effects against STAT3 signaling in breast cancer cells thus reducing the overall cancer cell aggressiveness [76]. Similarly, STAT1 also appears to have some inhibitory effects against STAT3 signaling [77]. As we have not been able to elucidate the exact mechanism of STAT3/ER interaction and the crosstalk with NFκB, these results necessitate an investigation into pathways that are not necessarily canonically known to be activated by the specific cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…STAT1 exerts its function of inhibiting tumor progression by regulating cell cycle regulators (e.g., p21WAF1 and p27KIP1) [25,26], proapoptotic proteins (e.g., Bcl-2 family members) [27,28], death receptors (e.g., FAS) [29], and angiostatic chemokines (e.g., CXCL10 and CXCL11) [30,31]. Both STAT3 and STAT1 participate in the JAK/STAT signaling pathway and antagonize each other, and TMUB1 has an inhibitory effect on STAT3 [32,33]. Therefore, we speculate that TMUB1 may inhibit HCC by promoting STAT1.…”
Section: Introductionmentioning
confidence: 99%